2015
DOI: 10.1038/nrn3921
|View full text |Cite
|
Sign up to set email alerts
|

Development and functions of the choroid plexus–cerebrospinal fluid system

Abstract: The choroid plexus (ChP) is the principal source of cerebrospinal fluid (CSF), which has accepted roles as a fluid cushion and a sink for nervous system waste in vertebrates. Various animal models have provided insight into how the ChP–CSF system develops and matures. In addition, recent studies have uncovered new, active roles for this dynamic system in the regulation of neural stem cells, critical periods and the overall health of the nervous system. Together, these findings have brought about a paradigm shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
400
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(417 citation statements)
references
References 158 publications
(181 reference statements)
15
400
0
2
Order By: Relevance
“…Choroidal BCSFB dysfunction underlies leukocyte infiltration, reduced neurogenesis, and cognitive decline in many neurological diseases [43]. In the current study, we found orthopedic surgery significantly induced C3 deposition in the choroid plexus.…”
Section: Discussionsupporting
confidence: 51%
“…Choroidal BCSFB dysfunction underlies leukocyte infiltration, reduced neurogenesis, and cognitive decline in many neurological diseases [43]. In the current study, we found orthopedic surgery significantly induced C3 deposition in the choroid plexus.…”
Section: Discussionsupporting
confidence: 51%
“…The blood-CSF barrier (BCB) lies between the choroid plexus vessels in circumventricular organs (CVOs) and the CSF (Choi and Kim, 2008;Benarroch, 2011;Lun et al, 2015). The CVOs are found to be located around the cerebral ventricles, and the CVOs with BCB are characterized by lack of BBB properties (Choi and Kim, 2008;Benarroch, 2011).…”
Section: Downloaded Frommentioning
confidence: 99%
“…We then searched for the expression of GAS1 in pericytes. These cells directly surround the endothelial cells (Lun et al 2015b), and there is a report showing that the pericytes of the CP express the receptor for SHH and respond to it, at least during development (Nielsen and Dymecki 2010). We used the anti-neural/ glial antigen 2 (NG2)-antibody which marks oligodendrocyte progenitor cells and pericytes (Nielsen and Dymecki 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The CP consists of an epithelial and a stromal layer, the first one is a monolayer of epithelial cells that surrounds a stromal layer mainly composed by fenestrated capillaries and to a lesser extent by other cell types (Lun et al 2015b). …”
Section: Gas1 Is Expressed In the Stroma Of The Choroid Plexusmentioning
confidence: 99%